2014
DOI: 10.3892/br.2014.325
|View full text |Cite
|
Sign up to set email alerts
|

Association between LGALS2 3279C>T and coronary artery disease: A case-control study and a meta-analysis

Abstract: Coronary artery disease (CAD) has become the main cause of mortality worldwide. Lectin galactoside-binding soluble-2 () is involved in the cytokine lymphotoxin-α (LTA) cascade that may influence the progress of CAD. The aim of the present study was to assess the association between the 3279C>T (rs7291467) polymorphism and CAD. A total of 562 cases and 572 controls were recruited to examine the association. A systematic meta-analysis was performed to evaluate the contribution of 3279C>T polymorphism to the risk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 40 publications
(46 reference statements)
0
3
0
Order By: Relevance
“…This single nucleotide polymorphism is located over 380 kb away from the LGALS2 -eMS cg07855639. However, subsequent studies in other Asian and European populations provided mixed results [5661]. Studies even found the TT genotype, which leads to lower levels of galectin-2, to be associated with more severe coronary stenosis [62] and higher levels of C-reactive protein [60].…”
Section: Discussionmentioning
confidence: 99%
“…This single nucleotide polymorphism is located over 380 kb away from the LGALS2 -eMS cg07855639. However, subsequent studies in other Asian and European populations provided mixed results [5661]. Studies even found the TT genotype, which leads to lower levels of galectin-2, to be associated with more severe coronary stenosis [62] and higher levels of C-reactive protein [60].…”
Section: Discussionmentioning
confidence: 99%
“…Resent meta-analysis also demonstrated the association between rs7291467 SNP and MI. 42 This genetic substitution seemed to affect the transcriptional level of galectin-2, which led to altered secretion of LTA, thereby affecting the degree of inflammation. We also found that galectin-2 binds to tubulins, which are important components of microtubules, suggesting a role in intracellular trafficking ( Figure 1).…”
Section: The First Gwas In a Japanese Populationmentioning
confidence: 98%
“…It is well known that CAD has multiple causes including environmental and genetic factors (He et al, 2005;Roger et al, 2012). Recently, several studies have indicated that genetic polymorphisms, including those of the MEF2A, CRP, LGALS2, GP78, and MMP-9 genes, are associated with increased risk of CAD (Cha et al, 2014;Foroughmand et al, 2014;Ghaffari et al, 2014;Lian et al, 2014;Opstad et al, 2014).…”
Section: Introductionmentioning
confidence: 99%